The invectives of Sallust and Cicero : critical edition with introduction, translation, and commentary - Novokhatko, Anna A., 1978- (Sozomena (Berlin, Germany), 2009)
This work covers the history of the text of the invectives of Sallust against Cicero and of Cicero against Sallust. Though these speeches seem unsophisticated to some, they are in fact of considerable importance. The question of the authenticity of both invectives, especially of the invective against Cicero, considered in the book diachronically, has long troubled scholars, commencing with Quintilian's quotation from the text as though it were authentic. This dispute continues down to our own time. In all probability, both invectives are a product of the rhetorical schools of Rome, as students.